Shifts in the Active Rhizobiome Paralleling Low Meloidogyne chitwoodi Densities in Fields Under Prolonged Organic Soil Management - Harkes, Paula; van Steenbrugge, Joris Johannes Matheus; van den Elsen, Sven Johannes Josephus; Suleiman, Afnan Khalil Ahmad; de Haan, Johannes Jan; Holterman, Martijn Hermanus Maria; Helder, Johannes (Frontiers in Plant Science, 2020)
Plants manipulate their rhizosphere community in a species and even a plant life stage-dependent manner. In essence plants select, promote and (de)activate directly the local bacterial and fungal community, and indirectly representatives of the next trophic level, protists and nematodes. Consequently, plants enlarge the pool of bioavailable nutrients and maximize local disease suppressiveness within the boundaries set by the nature of the local microbial community. MiSeq sequencing of specific variable regions of the 16S or 18S ribosomal DNA is widely used to map microbial shifts. As current RNA extraction procedures are time-consuming and expensive, the rRNA-based characterization of the active microbial community is taken along less frequently. Recently, we developed a relatively fast and affordable protocol to extract rDNA and rRNA simultaneously from soil. Here we investigated the long-term impact of soil management regimes, two conventional and an organic, on soil biota in fields naturally infested with the Columbian root-knot nematode Meloidogyne chitwoodi, with pea as the main crop. Large differences were observed between resident (rDNA) and active (rRNA) microbial communities. The bacterial community was most affected by the main crop, and unweighted and weighted UniFrac analyses (explaining respectively 16.4% and 51.3% of the observed variation) pointed at a quantitative rather than a qualitative shift. LEfSe analyses were employed for each of the four organismal groups to taxonomically pinpoint the effects of soil management. Concentrating on the bacterial community in the pea rhizosphere, organic soil management resulted in a remarkable activation of members of the Burkholderiaceae, Enterobacteriaceae, and Pseudomonadaceae. Prolonged organic soil management was also accompanied by significantly higher densities of bacterivorous nematodes, whereas levels of M. chitwoodi had dropped drastically. Though present and active in the fields under investigation Orbiliaceae, a family harboring numerous nematophagous fungi was not associated with the M. chitwoodi decline. A closer look revealed that a local accumulation and activation of Pseudomonas, a genus that includes a number of nematode-suppressive species, paralleled the lower M. chitwoodi densities. This study underlines the relevance of taking along both resident and active fractions of multiple organismal groups while mapping the impact of e.g. crops and soil management regimes.